Pengaruh Model Problem Based Learning Berbantuan Media Wayground terhadap Hasil Belajar Peserta Didik dalam Pembelajaran IPAS di Sekolah Dasar - Tyara Avillya Santika; Acep Roni Hamdani; Nurul Fazriyah (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to determine the influence of the Wayground media-assisted Problem-Based Learning (PBL) model, to assess the improvement in students' learning outcomes, and to measure the magnitude of the effect of implementing this model on students' learning outcomes in 4th-grade elementary school IPAS (Science and Social Studies) learning. This study employed a quantitative approach with an experimental method and a quasi-experimental design. The research subjects were 4th-grade elementary school students, divided into an experimental class and a control class. Data collection was conducted through learning outcome tests, observations, and documentation. The data were analyzed using statistical tests to determine the difference in learning outcome improvement between the two groups. This study is expected to prove that the application of the Wayground media-assisted Problem-Based Learning (PBL) model can significantly improve students' learning outcomes compared to conventional learning. Furthermore, the results of this study are expected to serve as a reference for teachers in implementing more innovative, interactive, and student-centered learning, thereby enhancing the quality of IPAS learning in elementary schools.